2018
DOI: 10.1021/acscatal.8b03484
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Activity Relationships in Alkane Dehydrogenation on γ-Al2O3: Site-Dependent Reactions

Abstract: A promising route to produce olefins, the building blocks for plastics and chemicals, is the nonoxidative dehydrogenation of alkanes on metal oxides, taking advantage of the Lewis acid−base surface functionalities of the oxides. However, how alkane dehydrogenation activity depends on the strength of surface acid−base site pairs is still elusive. In this work, we provide fundamental insights into the reaction mechanisms of propane dehydrogenation on different facets of γ-Al 2 O 3 and develop structure−activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
96
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 82 publications
(100 citation statements)
references
References 47 publications
4
96
0
Order By: Relevance
“…It is clear that propane and H 2 are weakly physisorbed on the surface without bond formation. Furthermore, the calculated adsorption energies fall within the typical ranges of the physisorption energies of propane and H 2 (−0.2 ~ −0.4 eV and − 0.05 ~ −0.2 eV for propane and H 2 , respectively), as has been observed on metal surfaces 68‐70 and other oxide surfaces 12,17 …”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…It is clear that propane and H 2 are weakly physisorbed on the surface without bond formation. Furthermore, the calculated adsorption energies fall within the typical ranges of the physisorption energies of propane and H 2 (−0.2 ~ −0.4 eV and − 0.05 ~ −0.2 eV for propane and H 2 , respectively), as has been observed on metal surfaces 68‐70 and other oxide surfaces 12,17 …”
Section: Resultssupporting
confidence: 75%
“…Metal‐oxide surfaces usually have a high degree of site heterogeneity, 17 which provides an opportunity for understanding site‐dependent catalysis and designing optimal catalysts under the guidance of structure–activity relationships 64 . On the outermost layer of the pristine Ga 2 O 3 (100) surface, there exist three distinct types of ions, namely, octahedrally coordinated Ga(o), tetrahedrally coordinated Ga(t), and threefold coordinated O, as shown in Figure 1a.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it is well-known that the amount of different acidic sites of catalyst are the key to affect catalytic activity in alkane dehydrogenation reaction. 37 The isobutane conversion rate vs. the number of different acidic sites on the basis of Table 2 were plotted (Fig. 10).…”
Section: Nh 3 -Tpd Analysismentioning
confidence: 99%
“…Alumina can be obtained in both amorphous and crystalline form, and increasing the crystallinity improves thermal stability. [12] It was found that nano-shape morphology enhances the metal dispersion, thus improving the interaction with the support. The modification of physical and chemical properties affects the interaction of metal as well as interaction of reactants and products.…”
Section: Introductionmentioning
confidence: 99%
“…[11] Recently another study showed the structureactivity relationship on gamma-alumina. [12] It was found that nano-shape morphology enhances the metal dispersion, thus improving the interaction with the support. For dehydrogenation reaction, the morphology effect has also been studied to understand the structure-activity relationship.…”
Section: Introductionmentioning
confidence: 99%